2021
DOI: 10.1177/2040622320986721
|View full text |Cite
|
Sign up to set email alerts
|

Decreased numbers and sex-based differences of circulating regulatory T cells in patients with seropositive undifferentiated arthritis

Abstract: Aims: CD4+ T cells play crucial roles as both mediators and regulators of the pathogenesis of rheumatoid arthritis (RA). However, the characteristics of CD4+ T cell subpopulations in the earliest stage of RA development remain unclear. Hence, we determined the proportions and absolute counts of circulating CD4+ T cell subsets in patients with seropositive undifferentiated arthritis (SUA), the early and preclinical stage of RA. Methods: Peripheral blood samples and clinical information were collected from 177 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
7
2
Order By: Relevance
“…After washing, the samples were analyzed by flow cytometry. The percentages and absolute counts of CD4 + T cell subpopulations were determined using BD Multitest software (BD Biosciences) (Niu et al, 2021).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…After washing, the samples were analyzed by flow cytometry. The percentages and absolute counts of CD4 + T cell subpopulations were determined using BD Multitest software (BD Biosciences) (Niu et al, 2021).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…The substantial defect in the frequency of Tregs has previously been identified in RA patients. 13 , 14 , 53 However, the flow cytometry results showed no statistically significant difference in Treg frequencies between HC and RA patients, which might be related to the different effects of conventional and biological DMARDs on Tregs in RA patients. 54 – 57 A number of studies have shown that treatment of RA patients with some but not all of DMARDs, such as methotrexate, tumor necrosis factor-α inhibitors (TNF-αi), adalimumab, and etanercept can restore the regulatory functions of Tregs and increase the frequency of these cells through various mechanisms.…”
Section: Discussionmentioning
confidence: 85%
“… 2 , 4 , 10 – 12 In addition, a consistent number of studies have reported a decrease in the percentage of circulating Tregs in RA patients compared to healthy individuals. 13 , 14 Clinical treatment of RA, essentially involves the use of medications to improve disease progression and minimize disease activity. The majority of these medications have shown adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…BD TruCount tubes were used to determine the absolute counts of total CD4 + T cells in the peripheral blood. The absolute numbers of CD4 + T subsets (e.g., CD4 + Treg cells) were then calculated with the following calculation formula: Number of CD4 + T subsets = Number of CD4 + T cells × Percentage of CD4 + T subsets [24].…”
Section: Measurements Of Lymphocyte Subsets and Cytokines In Serummentioning
confidence: 99%